Upaya Menormalisasikan LGBT oleh Aktivis di Amerika Serikat: Perjuangan dan Tantangan - Sambas, Rizki Fadilla; Hutajulu, Rahel Arthaida; Farhana, Safira; Purba, Putri Aulia; Siregar, Frederik Noel; Sianturi, Lady Yohana; Sinaga, Javanya (Polyscopia, 2024)
This research examines efforts to normalize the LGBT community by activists in the United States, with a focus on the struggles and challenges they face. Through qualitative analysis of various advocacy strategies, campaigns and policies implemented, this study reveals how LGBT activism seeks to create a more inclusive and accepted environment in society. This research also explores the role of the media, government agencies and non-government organizations in supporting or hindering this normalization process. Challenges faced include cultural resistance, institutional discrimination, and changing political and social dynamics. The research findings show that despite significant progress in the recognition of LGBT rights, activism continues to face major challenges that require a strategic and collaborative approach to overcome. In doing so, this research provides in-depth insight into the complexities of the LGBT normalization struggle in the United States and suggests policies and practices that can accelerate the process of social inclusion.